GONG Inter-site Hα flare comparison - Giersch, Owen (IOP Publishing Ltd, 2013)
A challenge of the past few decades for the Solar Observing Optical Network (SOON), operated by the United States Air Force Weather Agency (AFWA), has been to obtain consistent flare brightness reporting for the same flare from different sites. Flare area is usually considered to be a more reliable measure, but significant variation of values between sites still occurs. The Global Oscillation Network Group (GONG) deployed a Hα patrol system in 2010. This provides a modern system with near identical equipment to compare flares from six different sites. The classification of flares and techniques of flare measurement will be briefly discussed. The results presented here suggest that even though different GONG sites report different flare areas and brightness, for some sites they vary in a consistent way allowing correction factors to be applied.